Peran Usia Pelaku dalam Sikap Masyarakat Awam Terhadap Pelaku Kejahatan Seksual Pada Anak - Fathul Lubabin Nuqul (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2013)
Sexual abuse is a serious crime because of its lasting impact on the victim. Perpetrators of sex crimes should be punished severely. However, background of sex offenders, such as age, would cause sex offender’s sentence to be reduced or just simply receive guidance. The purpose of this study was to look at the extent to which students are imprisonment or pro rehabilitation (endogenous variable). Additionally, age, severity of the crime were used as exogenous variables. 240 students were involved in this study. The analysis of the data using structural equation models showed agreement between data and theory. Furthermore, the results of regression analysis showed that criem severity variable has a strong influence on the pro rehabilitation, while the age of sex offenders has an indirect effect on the pro sentenced to prisonKey word: Criminal Responsibility, seriousness of crime, punitiveness